Clinical outcomes at 12 months and risk of inflammatory bowel disease in patients with an intermediate raised fecal calprotectin: a 'real-world' view. Issue 6 (6th June 2016) - McFarlane, Michael; Chambers, Samantha; Malik, Ahmad; Lee, Bee; Sung, Edmond; Nwokolo, Chuka; Waugh, Norman; Arasaradnam, Ramesh
Abstract : Objectives: A recent systematic review confirmed the usefulness of fecal calprotectin (FC) in distinguishing organic (inflammatory bowel disease (IBD)) from non-organic gastrointestinal disease (irritable bowel syndrome (IBS)). FC levels <50 μg/g have a negative predictive value >92% to exclude organic gastrointestinal (GI) disease. Levels >250 μg/g correlate with endoscopic IBD disease activity; sensitivity 90%. We aimed to determine clinical outcomes in intermediate raised FC results (50–250 μg/g). Setting: Primary care general practices in Coventry and Warwickshire, and 3 secondary care hospitals. Participants: 443 FC results in adults (>16 years old) were reviewed from July 2012 to October 2013. Clinical data was collected from hospital databases and general practitioners. Long-term clinical data was available in 41 patients (out of 48). Primary and secondary outcome measures: The number of new diagnoses of IBD, IBS and other diagnoses for the intermediate group. The number referred and discharged from secondary care. Results: A new IBD diagnosis was made in 19% (n=8) of intermediate results (1% of normal and 38% of raised results). 5% (n=2) of intermediate results had known IBD in remission. A new IBS diagnosis was made in 27% (n=11) of intermediate results, while 34% (n=14) remained undiagnosed, although 8 of these were not referred to secondary care. Conclusions: FC testing remains useful in aiding diagnosis of organic GI conditions. However, unlike negative and strongly positive FC results, intermediate FC results lead to a mixture of diagnoses. The OR of a new diagnosis of IBD for an intermediate result compared to normal FC result was 26.6, while an intermediate FC result gave an OR of 0.54 for a new IBS diagnosis compared to normal FC. For intermediate FC results, 1 in 3 patients remained in secondary care after 12 months with an OR of 3.6 compared to a normal FC result.